Prospecção fitoquímica de ativos em extratos e frações originados de folhas de Azadirachta indica A. JUSS. visando atividade antimicrobiana - Galeane, Mariana Cristina [UNESP] (2015)
Azadirachta indica Azadirachta indica Azadirachta indica Azadirachta indica Azadirachta indica Azadirachta indica A. Juss A. JussA. Juss, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or margosa, belongs to the family, popularly known as neem or ...